A two-dimensional bilayered Dion–Jacobson-type perovskite hybrid with a narrow bandgap for broadband photodetection. Issue 6 (21st February 2020) - Fu, Dongying; Yuan, Jianrong; Wu, Shichao; Yao, Yunpeng; Zhang, Xinyuan; Zhang, Xian-Ming
Abstract : A unique 2D bilayered Dion–Jacobson type perovskite hybrid semiconductor shows broadband photodetection. Abstract : A novel 2D bilayered Dion–Jacobson (DJ) type hybrid perovskite, (2-methyl-1, 5-diaminopentane)(methylammonium)Pb2 I7 (1 ), with a narrow band gap of 1.96 eV has been reported, and such a DJ-type hybrid has been for the first time demonstrated to exhibit broadband photoresponsive properties with high photoresponsivity (13 A W −1 under a 10 V bias) and considerable switching ratios (>10 3 ).